Inhibition of hyaluronan synthesis attenuates pulmonary hypertension associated with lung fibrosis. (17th August 2017) - Collum, Scott D; Chen, Ning‐Yuan; Hernandez, Adriana M; Hanmandlu, Ankit; Sweeney, Heather; Mertens, Tinne C J; Weng, Tingting; Luo, Fayong; Molina, Jose G; Davies, Jonathan; Horan, Ian P; Morrell, Nick W; et al.
Abstract : Background and Purpose: Group III pulmonary hypertension (PH) is a highly lethal and widespread lung disorder that is a common complication in idiopathic pulmonary fibrosis (IPF) where it is considered to be the single most significant predictor of mortality. While increased levels of hyaluronan have been observed in IPF patients, hyaluronan‐mediated vascular remodelling and the hyaluronan‐mediated mechanisms promoting PH associated with IPF are not fully understood. Experimental Approach: Explanted lung tissue from patients with IPF with and without a diagnosis of PH was used to identify increased levels of hyaluronan. In addition, an experimental model of lung fibrosis and PH was used to test the capacity of 4‐methylumbeliferone (4MU), a hyaluronan synthase inhibitor to attenuate PH. Human pulmonary artery smooth muscle cells (PASMC) were used to identify the hyaluronan‐specific mechanisms that lead to the development of PH associated with lung fibrosis. Key Results: In patients with IPF and PH, increased levels of hyaluronan and expression of hyaluronan synthase genes are present. Interestingly, we also report increased levels of hyaluronidases in patients with IPF and IPF with PH. Remarkably, our data also show that 4MU is able to inhibit PH in our model either prophylactically or therapeutically, without affecting fibrosis. Studies to determine the hyaluronan‐specific mechanisms revealed that hyaluronan fragments result in increased PASMC stiffness and proliferation but reduced cell motility in a RhoA‐dependent manner. Conclusions and Implications: Taken together, our results show evidence of a unique mechanism contributing to PH in the context of lung fibrosis.